Quantification of promoting efficiency and reducing toxicity of Traditional Chinese Medicine: A case study of the combination of Tripterygium wilfordii hook. f. and Lysimachia christinae hance in the treatment of lung cancer - Zhang, Xiaoyi; Wang, Kexin; Dai, Hui; Cai, Jieqi; Liu, Yujie; Yin, Chuanhui; Wu, Jie; Li, Xiaowei; Wu, Guiyong; Lu, Aiping; Liu, Qinwen; Guan, Daogang (Frontiers in Pharmacology, 2022)
Traditional Chinese medicine (TCM) usually acts in the form of compound prescriptions in the treatment of complex diseases. The herbs contained in each prescription have the dual nature of efficiency and toxicity due to their complex chemical composition, and the principle of prescription is usually to increase efficiency and reduce toxicity. At present, the studies on prescriptions have mainly focused on the consideration of the material basis and possible mechanism of the action mode, but the quantitative research on the compatibility rule of increasing efficiency and reducing toxicity is still the tip of the iceberg. With the extensive application of computational pharmacology technology in the research of TCM prescriptions, it is possible to quantify the mechanism of synergism and toxicity reduction of TCM formula. Currently, there are some classic drug pairs commonly used to treat complex diseases, such as Tripterygium Wilfordii with Desmodium styracifolium for lung cancer, Aconiti Lateralis Preparata with Radix Glycyrrhizae in the treatment of coronary heart disease, and Radix Aconiti with Radix Stephaniae Tetrandrae on rheumatoid arthritis, but there is a lack of systematic quantitative analysis model and strategy to quantitatively study the compatibility rule and potential mechanism of synergism and toxicity reduction. To address this issue, we designed an integrated model of efficacy and toxicity which based on matrix decomposition and effect propagation, to detect the possible mechanisms of synergism and attenuation of Tripterygium Wilfordii and Lysimachia christinae in the treatment of lung cancer. The results showed that the compatibility of Tripterygium Wilfordii and Lysimachia christinae could increase the efficacy and decrease the toxicity of lung cancer treatment through MAPK pathway and PD-1 checkpoint pathway in lung cancer.